Synthetic fluid inclusions XXII: Properties of H2O-NaCl ± KCl fluid inclusions trapped under vapor- and salt-saturated conditions with emphasis on the effect of KCl on phase equilibria. (1st March 2020) - Lecumberri-Sanchez, Pilar; Luo, Maocheng; Steele-MacInnis, Matthew; Runyon, Simone E.; Matthew Sublett, D.; Klyukin, Yury I.; Bodnar, Robert J.
Abstract: Hydrodynamic and thermodynamic modeling of fluid evolution in shallow magmatic hydrothermal systems based on phase equilibria for the system H2 O-NaCl predicts that the fluid becomes halite saturated at some point in its evolution. A review of the published fluid inclusion data also supports halite saturation in these systems. In this study, we synthesized fluid inclusions at known pressure-temperature-composition (PTX) conditions in the H2 O-NaCl and H2 O-NaCl-KCl systems such that vapor + halite or liquid + vapor + halite existed at the time of trapping. Our results show that fluid inclusions trapped in the liquid + vapor + halite field in experiments along an evolving temperature path best match the phase ratios and thermometric behavior of fluid inclusions commonly reported in magmatic-hydrothermal systems (particularly in porphyry-style deposits). These results are consistent with the hypothesis that magmatic-hydrothermal fluids in porphyry settings are commonly trapped under conditions of liquid + vapor + halite equilibrium, which in turn has consequences for fluid flow and mineralization. Our results also show that the presence of KCl in the system significantly improves the agreement between microthermometric behaviors reported in natural systems and experimental results. The major effect of adding KCl is to increase the thermodynamic variance (degrees of freedom) of coexistence of liquid + vapor + halite from univariant in the system H2 O-NaCl to divariant (occupying an area, rather than a line, in pressure–temperature space). Simulations based on the system H2 O-NaCl predict that halite saturation occurs predominantly in the vapor + halite field with localized halite precipitation during the transition from the liquid + vapor to the vapor + halite field. By rendering the liquid + vapor + halite coexistence space as divariant, the addition of KCl also prevents an abrupt termination of liquid stability upon intersecting the liquid + vapor + halite boundary. Simulations using the system H2 O-NaCl commonly predict pressure–temperature pathways constrained to the univariant liquid + vapor + halite curve, owing to volumetric and latent heat constraints. In contrast, the presence of KCl relaxes these constraints and expands the ranges of pressure and temperature over which liquid, vapor and halite can coexist. This phenomenon has major implications for the chemical and hydrological evolution in magmatic-hydrothermal systems as related to the ability of fluids to transport metals (ore deposition) and the potential loss of porosity/permeability as a result of salt and quartz precipitation.